2005
DOI: 10.1051/0004-6361:20053511
|View full text |Cite
|
Sign up to set email alerts
|

A library of high resolution synthetic stellar spectra from 300 nm to 1.8 ${\rm \mu}$m with solar andα-enhanced composition

Abstract: Libraries of stellar spectra are fundamental tools for the study of stellar populations, and both empirical and synthetic libraries have been used for this purpose. In this paper, a new library of high resolution synthetic spectra is presented, ranging from the near-ultraviolet (300 nm) to the near-infrared (1.8 µm). The library spans all the stellar types that are relevant to the integrated light of old and intermediate-age stellar populations in the involved spectral region (spectral types F through M and al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
502
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 401 publications
(511 citation statements)
references
References 80 publications
5
502
2
2
Order By: Relevance
“…other Fe-sensitive indices, as a result of its sensitivity to Ti abundance, which is enhanced in the α-enhanced models Johansson et al 2012). The same applies to Fe 4531 for which we also see that the α-enhanced model lines are closer to the corresponding base model lines (see also figure 9 in ) This beahviour is also seen for fixed [Fe/H], as Mg, i.e an important electron donor, tends to lower the true continuum (Barbuy et al 2003;Coelho et al 2005).…”
Section: Line-strengths With Varying Abundance Ratiossupporting
confidence: 72%
See 2 more Smart Citations
“…other Fe-sensitive indices, as a result of its sensitivity to Ti abundance, which is enhanced in the α-enhanced models Johansson et al 2012). The same applies to Fe 4531 for which we also see that the α-enhanced model lines are closer to the corresponding base model lines (see also figure 9 in ) This beahviour is also seen for fixed [Fe/H], as Mg, i.e an important electron donor, tends to lower the true continuum (Barbuy et al 2003;Coelho et al 2005).…”
Section: Line-strengths With Varying Abundance Ratiossupporting
confidence: 72%
“…The Coelho et al (2005) theoretical library covers effective temperatures, T eff , between 3500 and 7000 K, surface gravities, log g, between +0.0 and +5.0, iron metallicities, [Fe/H] The accuracy of this library has been assessed in Martins & Coelho (2007), who showed that this library had the highest success in reproducing spectral features of observed stars among the theoretical libraries analysed in that work. The spectra have higher spectral resolution and wavelength coverage than MILES, therefore they were convolved with a gaussian kernel and were resampled to match MILES spectral resolution, dispersion and wavelength coverage.…”
Section: Theoretical Stellar Spectral Librarymentioning
confidence: 99%
See 1 more Smart Citation
“…The spectrum synthesis code used is described in Barbuy et al (2003) and Coelho et al (2005). The stellar parameters reported in Table A.1 were adopted from the detailed analyses by Zoccali et al (2006) and Lecureur et al (2007) for 43 bulge field red giants.…”
Section: Calculations Of C N and O Abundancesmentioning
confidence: 99%
“…for λ < ∼ 3000Å) we can presently count on important theoretical datasets covering the full parameter space to reproduce stellar spectral energy distribution (SED) across the whole H-R diagram, at wavelength resolution typically better than λ/∆λ > ∼ 20 000 (see Bertone, 2005, for an exhaustive review on this subject). Among others, these include the work of Rodríguez-Merino et al (2005) (Uvblue spectral library), Gustafsson et al (2003) (Marcs model grid), Munari et al (2005), Hauschildt et al (1999) (the NextGen library), and Coelho et al (2005).…”
Section: Introductionmentioning
confidence: 99%